Women Workers' Protection in the Job Creation Law Feminist Legal Theory Perspective - Indra Firmansyah; Putra Aji Widia Priambodo; Esti Kanti Pertiwi; Arjuna Al Ichsan Siregar (Universitas Kuningan, 2021)
This study aims to find how women workers' protection is linked to a feminist legal approach, referring to the job creation law. The study revealed there was no improvement in the law. It tended to be detrimental, especially the discussion of three articles: 59, 79, and 81. Feminist Legal Theory sees the need for a breakthrough, the making and enacting laws against women. This is to eliminate discrimination, marginalization, and subordination by law against women. The study employed normative juridical research, involving the statute and conceptual approaches. The data were collected by a literature study involving descriptive data analysis techniques. The study showed women workers' protection, the Job Creation Law has not improved. It is even more destructive, especially the regulation of limitation periods in employment contracts, weekly rest, and contract labour abolition.